Viabilidade econômica do uso do calcário na implantação de pomar de goiabeiras - Natale, William [UNESP]; Rozane, Danilo Eduardo [UNESP]; Prado, Renato de Mello [UNESP]; Romualdo, Liliane Maria [UNESP]; de Souza, Henrique Antunes [UNESP]; Hernandes, Amanda [UNESP] (Universidade Federal de Lavras (UFLA), 2010)
With the objective of studying the relationship between limestone doses and guava production, a field experiment was conducted on Oxisol soil in the town of Bebedouro-SP, from 1999 to 2006. The experimental design was randomized blocks with four replications. The limestone was used only once in 1999, at doses from zero, 1.85; 3.71; 5.56 and 7.41 t ha(-1). The guava production increased in response to the application of the acidity corrective. The accumulated production of fruits in successive years 2003, 2004, 2005 and 2006 were associated with economical doses of limestone of 1.6; 4.4; 7.2 and 7.2 t ha(-1) respectively.
Economical viability of the use of limestone for the establishment of guava orchard
Keywords: Psidium guajava L.; Soil acidity; limestone; economic dose